Trajectory Konstruksi Jilbab di Indonesia: Pertarungan Beragam Kepentingan - Laillia Dhiah Indriani (Program Studi Ilmu Komunikasi UII, 2023)
The Construction of the Hijab in Indonesia is often associated with religious aspects. Hijab is frequently used to indicate a person's level of piety. Based on this assumption, specific standards have emerged in society to judge women. However, the hijab is a religious symbol closely connected to cultural aspects. Over time, the construction of hijab has been monopolized by certain institutions, obscuring its original discourse closely tied to the culture. Social construction in society has influenced the meaning of hijab in Indonesia. Therefore, this research aims to unravel the trajectory of hijab in Indonesia and its socio-political implications. The theoretical framework employed is a social construction by Berger & Luckman. The research is conducted qualitatively, with data collected through literature review and documentation. The findings reveal that the hijab, a piece of cloth to cover the head, has transformed into a symbol of piety used as a commodity and a specific political symbol. The construction of hijab ultimately serves various interests due to the diverse contexts underlying its construction, as well as the actors and interests involved.